Labour and regional transition: sex-segregation, the absence of gender and the valorisation of masculinised employment in Gippsland, Australia. Issue 12 (2nd December 2021) - Farhall, Kate; Tyler, Meagan; Fairbrother, Peter
Abstract: This paper explores the place of gender in relation to labour and transition in regional development. A 'gendered lens' is applied to planning documents relating to the region of Gippsland, Australia. While previous research highlights the importance of accounting for gender in regional development, gendered analyses outside Europe are scarce. We argue that an apparent gender neutrality in planning documents in effect privileges masculinised elements of the economy. It means that current approaches to regional development, at best, reproduce the gendered status quo and, at worst, further re-entrench gender inequality in the region, with consequences for regional labour policy. Our findings have flow on effects for gender relations, and specifically for women, and economic policy in regions undergoing transition in Gippsland. We conclude that any regional policy that does not account for gendered realities and the lived experiences of women, ultimately fails the region.